Rolling Friction Torque in Ball-Race Contacts Operating in Mixed Lubrication Conditions - Mihaela Rodica D. Bălan; Luc Houpert; Ana Tufescu; Dumitru N. Olaru (Lubricants, 2015)
Based on a theoretical model and an experimental methodology for defining the friction torque for lubricated conditions in a modified thrust ball bearing having only three balls, the authors experimentally investigated the influence of the lubricant parameter Λ on friction torque for mixed IVR (isoviscous rigid) and EHL (elastohydrodynamic) lubrication conditions. The experiments were conducted using ball diameters of 3 mm, 3.97 mm and 6.35 mm loaded at 0.125 N, 0.400 N and 0.633 N. Two oils of viscosity 0.08 Pa·s and 0.05 Pa·s were used and rotational speed was varied in the range 60–210 rpm to obtain a lubricant parameter Λ varying between 0.3 and 3.2. The experiments confirmed that the measured friction torque can be explained using hydrodynamic rolling force relationships respecting the transition from an IVR to an EHL lubrication regime.